Climate variability on the south-eastern Tibetan Plateau since the Lateglacial based on a multiproxy approach from Lake Naleng – comparing pollen and non-pollen signals. (1st May 2015) - Opitz, Stephan; Zhang, Chengjun; Herzschuh, Ulrike; Mischke, Steffen
Abstract: A multi-proxy Lateglacial environmental record is described from Lake Naleng (31.10°N; 99.75°E, 4200 m above sea level), situated on south-eastern Tibetan Plateau to gain deeper insights into the hydrological and palaeoclimate development since 17.7 cal ka BP. Palynological reconstructions of variations in mean annual precipitation (MAP) and temperature (MAT), sedimentological data and sediment chemistry including weathering indicators provide a multi-faceted picture of local and regional environmental changes since the Lateglacial. Principal component analyses of all parameters provide information on interrelationships between each parameters, which help to evaluate their traceability to temperature and precipitation and to estimate their usability as proxy indicators for local and or regional variations. During the Lateglacial from 17.7 to 14.0 cal ka BP Lake Naleng experienced cold and dry climate conditions with low biological productivity and supply of unaltered fine-grained material due to the high supply of glacier milk. During the second half of the Lateglacial, climate conditions changed abruptly: increases in MAT (from −4 to −2.2 °C) and MAP (from 500 mm to 820 mm) between 14.0 and 13.0 cal ka BP indicate a climate amelioration. This time interval can be correlated to the Bølling/Allerød (B/A) warming period in the North Atlantic region and is followed by the Younger Dryas cold reversal indicated by abrupt decreases of MAT (from −2.2 to −5 °C) and MAP (from 820 to 650 mm). The onset of the Holocene at about 11.5 cal ka BP is indicated by rises in reconstructed MAT (from −5 to about −0.3 °C) and MAP (from 600 mm to 950 mm), which led to an increased supply of weathered material and higher biological productivity. Between 5.0 and 3.0 cal ka BP, MAT increases to about 0.2 °C and MAP rises to maximum values of about 1000 mm, followed by slightly decreasing MAT and MAP between 3.0 and 0 cal ka BP. The biogeochemical parameters (total organic carbon (TOC), C/N, δ 13 Corg ) and weathering indicators (e.g. the chemical index of alteration (CIA) and Sr/Ba) are directly (erosion of soils) or indirectly (changing provenance) related to moisture availability on the south-eastern TP and shows matching regional climate oscillations since the Lateglacial. In comparison to other Lateglacial records from the TP, MAP reconstructions from Lake Naleng indicate wetter climate conditions in the south-eastern part of the TP and dryer conditions farther away from moisture sources. Highlights: Comparison of multi-proxy downcore variations with reconstructed MAP and MAT. TOC, C/N, δ 13 Corg, CIA and Sr/Ba are related to changes of precipitation. Doubling of Holocene precipitation in comparison to Lateglacial conditions. Diminishing moisture availability from south to north on the eastern TP in the Holocene.